The Bay Area Functional Performance Evaluation-Task Oriented Assessment (BaFPE-TOA) in Severe Psychiatric Patients: A Psychometric Study - Ali Rashidian; Ashraf Karbalaei Nouri; Samaneh Hosseinzadeh; Hojjatollah Haghgoo (University of Social Welfare and Rehabilitation Sciences, 2018)
Objective The Bay Area Functional Performance Evaluation-Task Oriented Assessment (BaFPE-TOA) is a standard test developed by Williams and Bloomer in 1977-1978 in order to evaluate functional performance. This test consists of five tasks (sorting shells, money and marketing, home drawing, block design, kinetic person design), twelve parameters (memory for written and verbal instructions, organization, attention span, evidence of disorder, ability to abstract, completion, errors, efficiency, motivation and compliance, frustration tolerance, self-confidence, general affective impression) and three components (cognitive, affective, and performance components). The purpose of this study was to translate the BaFPE-TOA in Persian and to evaluate the face and content validity, and internal consistency in patients with severe psychiatric disorders. Materials & Methods A non-experimental and methodological study was carried out in Tehran in 2017; the study population included adult patients diagnosed with severe psychiatric disorders according to Diagnostic and Statistical Manual of Mental Disorders (DSM-5). In this study, demographic questionnaire and BaFPE test were used. Convenience Sampling was done on patients who were admitted to Razi Psychiatric Hospital. In order to prepare the Persian version, the translation of the BaFPE-TOA test was carried out in accordance with the International Quality of Life Assessment (IQOLA) project, which included: 1. Translation of the original version into Persian; 2. Review by translators and professors; 3. Translation quality; 4. Translation of the Persian version into English; and 5. Comparison of the English version with the original version. The Persian version was assigned to five experts to evaluate the content validity in terms of simplicity, relevance, clarity, and necessity. The face validity of the test was performed on three patients and two healthy individuals in order to find difficulties in the understanding of words and phrases, the appropriateness of the items, the likelihood of ambiguity and inadequate perceptions of expressions or the lack of meaning in words. After confirmation, a Persian version of the test was performed on 55 patients with severe psychiatric disorders who qualified the inclusion criteria. Inclusion criteria for this study included: 1. People with psychiatric disorders based on DSM-5 and are listed in the medical records by a psychiatrist; 2. Over 18 years old; 3. Complete consent to enter the study; 4. Aability to write and read; 5. Lack of comorbidity (mental retardation, drug abuse); 6. Lack of physical constraints affecting the performance of specified tasks; 7 Lack of visual impairment or severe hearing loss. Cronbach's alpha coefficient was used to evaluate the internal consistency with respect to the four options of the test. Data analysis was performed using SPSS v.16 software. Results Experts' opinions about the quality of translation and replacement of words in the translation process were according to the IQOLA method. The face validity of the test according to the experts' opinion and its association with healthy subjects and patients showed that the clarity and implementation of common language were of good quality. The content validity of the test was performed according to the opinion of the five experts in mental health; the Content Validity Ratio (CVR) and the Content Validity Index (CVI), were equal to one for all domains. The minimum acceptable value for content validity based on CVI and CVR indices was 0.80 and 0.99, respectively, which indicated validity of the content and the lack of impact of culture on the parameters, tasks, and components of the BaFPE-TOA test. The results of the Cronbach's alpha coefficient for all fields was related to the twelve functional parameters, the three components, and the five tasks; the efficiency parameter was above 0.7 (the minimum acceptable value), indicative of the good internal reliability of this test. Conclusion According to the experts' opinion, the Persian version of the BaFPE-TOA test has a proper translation, with acceptable face and content validity and internal consistency. Therefore, this test can be recommended for the evaluation of functional performance in patients with severe psychiatric disorders.